Workforce development and skill formation in Asia - Benson, John, 1948-; Gospel, Howard F.; Zhu, Ying, 1961- (New York : Routledge, 2013)
"Asia has undergone rapid transformation over the past several decades as many countries have embraced new technologies and the processes of globalisation. Focusing on a number of developed and developing Asian economies, this book explores the dynamics of workforce development and skill formation, and considers questions of both skills shortages and skills gaps"--
Workforce development in Asia / John Benson, Howard Gospel and Ying Zhu -- Workforce development in theory and practice / Howard Gospel -- Workforce development in Japan / John Benson -- Workforce development in South Korea / Chris Rowley and Kil-Sang Yoo -- Workforce development in Singapore / Chris Leggett -- Workforce development in Hong Kong / Sek Hong Ng and Olivia Ip -- Workforce development in China / Ying Zhu and Malcolm Warner -- Workforce development in Taiwan / Ying Zhu and Malcolm Warner -- Workforce development in India / Debashish Bhattacherjee and Errol D'Souza -- Workforce development in Malaysia / Nagiah Ramasamy and Chris Rowley -- Workforce development in Asia : a comparative analysis / Ying Zhu, John Benson and Howard Gospel.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Occupational training -- Asia; Skilled labor -- Training of -- Asia; Labor supply -- Asia; Labor and globalization -- Asia; Electronic books